2007
DOI: 10.1002/dneu.20555
|View full text |Cite
|
Sign up to set email alerts
|

BCL‐2 counteracts Doppel‐induced apoptosis of prion‐protein‐deficient Purkinje cells in the Ngsk Prnp0/0 mouse

Abstract: The pro-apoptotic factor BAX has recently been shown to contribute to Purkinje cell (PC) apoptosis induced by the neurotoxic prion-like protein Doppel (Dpl) in the prion-protein-deficient Ngsk Prnp(0/0) (NP(0/0)) mouse. In view of cellular prion protein (PrP(c)) ability to counteract Dpl neurotoxicity and favor neuronal survival like BCL-2, we investigated the effects of the anti-apoptotic factor BCL-2 on Dpl neurotoxicity by studying the progression of PC death in aging NP(0/0)-Hu-bcl-2 double mutant mice ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
22
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 69 publications
1
22
0
Order By: Relevance
“…Consequently, four studies have recently reported that cell death in N-terminal truncated overpressing mice and in the Nagasaki line is regulated in a Bcl-2/BAX manner (Heitz et al, 2008;Heitz et al, 2007;Li et al, 2007a;Nicolas et al, 2007) (see Table 1). Surprisingly, contradictory results have been obtained in the latter strain, regarding the contribution of BAX depletion to ataxic syndrome rescue (Dong et al, 2007;Heitz et al, 2007).…”
Section: Bcl-2/bax and Prp C -Truncated Mouse Modelsmentioning
confidence: 99%
“…Consequently, four studies have recently reported that cell death in N-terminal truncated overpressing mice and in the Nagasaki line is regulated in a Bcl-2/BAX manner (Heitz et al, 2008;Heitz et al, 2007;Li et al, 2007a;Nicolas et al, 2007) (see Table 1). Surprisingly, contradictory results have been obtained in the latter strain, regarding the contribution of BAX depletion to ataxic syndrome rescue (Dong et al, 2007;Heitz et al, 2007).…”
Section: Bcl-2/bax and Prp C -Truncated Mouse Modelsmentioning
confidence: 99%
“…Oxidative stress may play a role in Doppel-induced neuronal death since NOS activity is induced by Doppel in vitro and in vivo (Cui et al, 2003;Wong et al, 2001). Two independent groups have reported that BAX contributes to Doppel-induced apoptosis (Didonna et al, 2012;Heitz et al, 2007) and that BCL-2 antagonizes Doppel neurotoxicity (Heitz et al, 2008). Another work has observed that ectopic Doppel expression in the brain elicits neurodegeneration through the binding of two metalloproteinase namely the alpha-1-inhibitor-3 (α1I3) and the alpha-2-macroglobin (α2M) (Benvegnu et al, 2009).…”
Section: Notementioning
confidence: 99%
“…While investigating the involvement of the Bcl-2 family members in Dpl-mediated apoptosis of NP 0/0 Purkinje cells, these neurons were partially rescued in either Bax-deficient (NP 0/0 :Bax -/-) or bcl-2 overexpressing (NP 0/0 -Hu-bcl-2) double mutant mice, implying that Dpl triggers both Bax-dependent apoptosis and Bax-independent neurotoxic mechanisms in the NP 0/0 Purkinje cells. 1,6,7 Given that the scrapie-responsive gene Scrg1 is potentially associated with autophagy and is abnormally expressed in NP 0/0 Purkinje cells and prion-diseased neurons, 8 and that reactive oxygen species (ROS) can activate both apoptosis 9 and autophagy, 10,11 we examined the possible role of autophagy in Dpl-induced neuronal death. In NP 0/0 mice, robust autophagy was observed in Purkinje cells well before significant neuronal loss.…”
mentioning
confidence: 99%
“…This effect could convert an initial autophagic defensive reaction into a neurodegenerative mechanism. 1,6 Increased or continued requirements for autophagy coupled with an impairment in the late phases of autophagic flux (i.e., completion of the lysosomal degradation process) may lead to autophagic stress. 15 The leakage of hydrolases induced by membrane destabilization of autolysosomes and lysosomes could trigger apoptotic cascades.…”
mentioning
confidence: 99%
See 1 more Smart Citation